Integrated approach for the investigation of groundwater quality using hydrochemical and geostatistical analyses in Wadi Fatimah, western Saudi Arabia - Alshehri, Fahad; Abdelrahman, Kamal (Frontiers in Earth Science, 2023)
The Wadi Fatimah area suffers from a lack of freshwater resources, so this study aimed to analyze the groundwater in this region and evaluate its quality for irrigation and drinking purposes. Eleven water quality parameters, including pH, total dissolved solids (TDS), Ca2+, HCO−3, NO−3, F−, Cl−, K+, Mg2+, SO2−4, and Na+, were utilized to evaluate the quality of the water and produce a water quality index (WQI). These parameters were measured at 100 different chosen locations. The spatial distribution map revealed that all parameters are high in the southern part except K+. Using the correlation matrix, a high positive correlation is obtained among TDS, Cl−, Mg2+, and Ca2+ in addition to a high correlation among TDS with Cl− and Na+. From PCA analysis, PCA1, PCA2, and PCA3 represent about 52%, 12%, and 10% of all components along the study area, respectively. PCA1 has low variance than PCA2 and PCA3. The majority of the Southern region’s sites went from having extremely poor to poor water classifications and from poor to unsuitable water. However, the center part possesses exceptionally high-quality groundwater. According to the results from the current study’s water quality index, the presence of nitrate and fluoride in the groundwater samples was primarily responsible for their high WQI values. The statistics showed that a higher percentage of the population had poor drinking water due to direct pollutant release, agricultural effects, and excessive groundwater resource use. The study offers a groundwater quality modeling technique that is both affordable and replicable in other areas.